The Effects of Online Interactions on the Relationship Between Learning-Related Anxiety and Intention to Persist Among E-Learning Students with Visual Impairment - Oh, Yunjin; Lee, Soon (International Review of Research in Open and Distributed Learning, 2016)
This study explored whether learning-related anxiety would negatively affect intention to persist with e-learning among students with visual impairment, and examined the roles of three online interactions in the relationship between learning-related anxiety and intention to persist with e-learning. For this study, a convenience sample of e-learning students with visual impairment was collected in Seoul, Korea over three weeks from November to December 2012. One hundred and three students completed the survey via email or telephone. The results showed significant associations between learning-related anxiety and intention to persist with e-learning. Three types of online interactions had different roles in and effects on the relationship between learning-related anxiety and intention to persist. Suggestions for improving intention to persist among students with visual impairment and for facilitating online communications were discussed.